Spachelated intussusception a forgotten entity: Historical review and a case report - Praveen Mathur; Priyanka Mittal; Punit Parihar; Rahul Gupta (Wolters Kluwer Medknow Publications, 2022)
Intussusception of one or another type is frequently seen in children and is the most common cause of acute bowel obstruction. This pathology is usually promptly recognized and treated accordingly. But if untreated, this entity can have either of the two outcomes. The first one is death from peritonitis and resulting toxemia, which is the most common one. The second one is spontaneous elimination followed by auto-anastomosis and is extremely infrequent. We report one such case of this rare progression who was found to have old healed small bowel intussusception with luminal narrowing on exploration for acute bowel obstruction. We have also reviewed the world literature to understand the mechanism and circumstances under which this progression occurs.